Studying the Impact of Selected Listing on NASDAQ Stock Exchange on Enterprise Profits: Forecasting the Case of VinFast Manufacturing and Trading Company Limited - Tu Uyen, Tran; Thi Nhat Linh, Hoang (VNU Journal of Science: Policy and Management Studies, 2024)
Initial Public Offering (IPO) is considered a strategic decision of utmost importance for every business, especially companies that wish to list on the stock exchange. international. Using the Wilcoxon non-parametric test method, the study shows that IPO activities have a positive impact on the profits of businesses listed on the NASDAQ Global Select Market stock exchange in general and of VinFast in particular. At the same time, the author had proposed a number of solutions to increase the number of companies in Vietnam conducting IPOs on the international stock market as well as policies to help increase the profits enterprises listed on the international stock market of listed businesses.